The Influence of Direct Compensation and Indirect Compensation through Work Standard Variables as Intervening Variables on Employee Performance at Warung Ayam Goreng Nelongso Klampis, Surabaya - Reny Meliyana Sari; Hermien Tridayanti (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
The objectives of this study are: 1. To analyze whether direct compensation and indirect compensation have a significant effect on employee performance at Warung Ayam Goreng Nelongso Klampis, Surabaya. 2. To analyze whether direct compensation and indirect compensation have a significant effect on employee performance through work standard variables as an intervening variable at Warung Ayam Goreng Nelongso Klampis, Surabaya. 3. To analyze whether work standards have a significant effect on employee performance at Warung Ayam Goreng Nelongso Klampis, Surabaya. This research is using quantitative research methods in the form of associative. The population and samples in this study were 32 employees of Warung Ayam Goreng Nelongso Klampis, Surabaya. The sample technique in this study used a sampling census. The analysis technique chosen is The Structural Equation Model (SEM) using Partial Least Square (PLS). The results showed that there was a direct effect between Direct Compensation (X1) on Employee Performance (Y2) but was not significant with a p-value of 0.000 and a t value of 0.261, there is a direct influence between Direct Compensation (X1) on Employee Performance (Y2) through Work Standards (Y1) but less significant with a p-value of 0.000 and a t value of 0.218, there is a direct effect between Indirect Compensation (X2) on Employee Performance (Y2) through Work Standards (Y1) has a significant effect with a p-value of 0,000 and a t value of 0.000, there is a direct influence between Indirect Compensation (X2) on Employee Performance (Y2) which is significantly influential with a p-value of 0,000 and a t value of 0.000, there is a direct effect between Work Standards (Y1) on Employee Performance (Y2) a significant effect with a p-value of 0,000 and a t value of 0.000. The results of this study indicate that the variable Indirect Compensation has the strongest influence on Employee Performance compared to other variables.